STUDI EMISI CO2AKIBAT KEBAKARAN HUTAN DI PROVINSI RIAU (STUDI KASUS DI KABUPATEN SIAK) - A.Z. Nasution (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractThis research was aimed to analyze the CO2emissions due to forest fires that occurred inSiak Regency, Riau Province Indonesia in 2010 and to analyze the probability of forest fireoccurrence in Siak Regency using the available data. Fire and CO2 emissions in the area ofplantation forests are greater than in the area of natural forests. The amount of CO2emissionsdue to forest fires in 2010 varied between 107.260 Ton CO2 yr-1 in natural forests and151.600 Ton CO2 yr-1 in plantation forests. The amount of CO2emissions due to forest fires inthe peat land was 2.176 Ton CO2 yr-1. This value is mainly depending on the extent of theburned area in the year of 2010. Results of the logistic regression show the forest fires aremore likely to occur in degraded forests.